A Reply to Palmira - Lo Guercio, Nicolás Francisco (2013)
In “Philosophical Peer Disagreement” I argued that in order to properly account for the phenomenon of philosophical peer disagreement it is necessary to drop the ‘same evidence’ condition from the definition of epistemic peerage. The reason is the following: different philosophical perspectives might come with different commitments concerning the evidential role of the same piece of data, and it would be wrong to deny the status of epistemic peer to someone that is acquainted with the same data, even if he does not consider it plays an evidential role. However, on “On the Necessity of the Evidential Equality Condition For Epistemic Peerage,” Michele Palmira has developed some criticisms to these ideas. Here I defend my view from Palmira’s objections.